Does restaurant menu information affect customer attitudes and behavioral intentions? A cross-segment empirical analysis using PLS-SEM. (August 2016) - Fakih, Khodr; Assaker, Guy; Assaf, A. George; Hallak, Rob
Abstract: This research looks at how consumer desires for restaurant menu information including "nutritional information", "product characteristics", and "preparation and ingredients" influence customers' attitudes and behavioural intentions toward restaurants. A theoretically derived model is empirically tested on data collected from 293 customers from three segments of the restaurant sector − High-Scale, Mid-Scale and Low-Scale. Partial least squares structural equation modelling (PLS-SEM) and multigroup analysis confirms that the relationship between menu information and behavioural intentions is mediated by consumers' attitudes toward the restaurant. Furthermore, 'preparation and ingredients' and 'nutritional information' were the two strongest predictors of attitudes and behavioural intentions for high- and mid-scale restaurants, whereas 'product characteristics' was the most significant for low-scale restaurants. These findings present new knowledge on how different types of information drive consumers' purchase intentions across different segments of the industry.